Intrinsic Clocks - Daniela D. Pollak (Frontiers Research Topics, 2018)
"Intrinsic Clocks" presents an array of current research activities on intrinsic clocks and their contributions to biology and physiology. It elucidates the current models for the intrinsic clocks, their molecular components and key mechanisms as well as the key brain regions and animal models for their behavioral analysis. It provides a timely view on how these clocks guide behavior, and how their disruption may cause depressive-like behavior and impairment in cognitive functions. Thereby, any specific method by which the mood-related functions of the intrinsic clocks might be influenced bears therapeutic potential and has clinical interest. The importance of some of these mechanisms was highlighted by the 2017 award of the Nobel Prize in Physiology or Medicine to Jeffrey C. Hall, Michael Rosbash, and Michael W. Young for their discoveries of the genetic control of the daily biological rhythm. The key to the explanation was the discovery of transcription-translation feedback loops of the so-called "clock genes."